2021
DOI: 10.1037/trm0000293
|View full text |Cite
|
Sign up to set email alerts
|

The psychological and economic toll of the COVID-19 pandemic on Latina mothers in primarily low-income essential worker families.

Abstract: The COVID-19 pandemic will have widespread health, economic, and psychological consequences. Reports indicate the Latino community is particularly vulnerable to the economic and health risks of this pandemic as a consequence of systemic oppression. Latina mothers, in particular, are navigating the pandemic from their racialized, gendered, and classed positions while caring for children and families. These factors are likely to have a significant psychological toll. The sample consisted of 70 Latina mothers. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 48 publications
2
47
0
2
Order By: Relevance
“…In terms of the impact of COVID-19, participants experienced significant losses to employment and income. Our findings were consistent with previous research documenting an increased burden of the pandemic on women, who are more likely than men to adjust their employment to take on increased caregiving responsibilities, due to school and child care closures (Hibel et al, 2021;Morgan et al, 2021;Reichelt et al, 2020). Because many immigrants were ineligible for federal government benefits, women in our study relied on temporary relief funds providing cash assistance.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of the impact of COVID-19, participants experienced significant losses to employment and income. Our findings were consistent with previous research documenting an increased burden of the pandemic on women, who are more likely than men to adjust their employment to take on increased caregiving responsibilities, due to school and child care closures (Hibel et al, 2021;Morgan et al, 2021;Reichelt et al, 2020). Because many immigrants were ineligible for federal government benefits, women in our study relied on temporary relief funds providing cash assistance.…”
Section: Discussionsupporting
confidence: 90%
“…Racial and ethnic minority groups share the unequal burden of being more likely to be low-income essential workers [ 22 ] and unemployed [ 23 , 24 ], forcing these populations to make economic cutbacks during the pandemic [ 22 ], which induces elevated stress and anxiety [ 22 ]. Residential racial segregation has been also consistently linked with a variety of adverse health outcomes, underlying health conditions, and affects minoritized groups more than NHWs [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In their study of Bhutanese and Burmese refugees in the United States, Zhang et al (2021) noted that the three largest risk factors for contracting COVID-19 were being an essential worker, having an infected family member, and being female. Hibel et al (2021) also found that Latina mothers were particularly at risk due to their role in caring for children and family members in essential occupations.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Some studies have already confirmed that the risk of exposure to COVID-19 is most prevalent in essential worker families and immigrant communities. Hibel et al (2021) found that 72 percent of their Hispanic families contained at least one employed adult, of whom 91.7 percent were essential workers. Roberts et al (2020) discovered that essential workers were more likely than nonessential workers to be Black or Hispanic.…”
Section: Literature Reviewmentioning
confidence: 99%